Recent Developments in Pharmacological Effect, Mechanism and Application Prospect of Diazeniumdiolates - Li, Bin; Ming, Yue; Liu, Yao; Xing, Haiyan; Fu, Ruoqiu; Li, Ziwei; Ni, Rui; Li, Li; Duan, Dongyu; Xu, Jing; Li, Chen; Xiang, Mingfeng; et al. (Frontiers in Pharmacology, 2020)
Nitric oxide (NO) is a simple structured and unstable free radical molecule, which participates in the regulation of many pathophysiological processes. It functions both as a second messenger as an endogenous neurotransmitter. Diazeniumdiolates (NONOates) are a series of compounds containing the functional parent nuclear structure of [N(O)NO]—, which are the most widely studied NO donors. NONOates are unstable and easy to release NO in physiological conditions. The biomedical applications and drug development of NO donor have attracted the scientists' attention in recent years. In this review, recent advances in NONOates research are highlighted in terms of chemical structures, molecular characters, pharmacological effects, and biomedical application prospects.